Pengaruh Penggunaan Alat peraga Terhadap Minat Belajar Siswa Kelas 5 dalam Pembelajaran IPA di MI Islamiyah Babakan - Heni Septi Riani (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
This research aims to find out: 1) Is there an effect of using teaching aids on the learning mint of grade 5b students of MI Islamiyah Babakan in science subjects. 2) How much influence the use of teaching aids has on the learning mint of grade 5b students of MI Islamiyah Babakan in science subjects. The type of research conducted is qualitative research using the pre-experimental design method using observation and interview techniques. The object of this research is class 5b students of MI Islamiyah Babakakn Kec. Baksiu Kab. Tegal with a total of 22 students. The results obtained show that the success of the learning process is reviewed from the aspect of grade completeness and student activeness in learning science. In class 5b, both aspects have been fulfilled when science learning is carried out with the help of teaching aids. All students were very enthusiastic while following the learning from beginning to end. It is different when learning without teaching aids, only some are always active until the end of learning. So the use of teaching aids has a big influence on students' interest in learning science subjects.